Analysis of the current status and influencing factors of moral courage among operating room nurses in Southwest China: a multi-center study - Xiao Hu; Yu Long; Chenfang Wang; Jianping Yi; Feng Peng; Yidi Chen (BMC Nursing)
Abstract Background Moral courage is crucial for nurses to act ethically despite professional risks. Operating room (OR) nurses frequently encounter ethical dilemmas, requiring a balance between personal convictions and institutional policies. This study investigates the current status of moral courage among OR nurses in Southwest China and explores key influencing factors. Materials and methods The cross-sectional, multi-center study was conducted from April to May 2024. A total of 482 operating room nurses from 16 hospitals in Southwest China were surveyed. The nurses were assessed using a self-designed demographic questionnaire, the Nurses’ Moral Courage Scale (NMCS), the Psychological Empowerment Scale (PES), and the Hospital Ethical Climate Survey (HECS). Statistical analyses, including Spearman’s rho and multiple linear regression, were used to explore the relationships between nurses’ moral courage and various influencing factors, such as age, educational level, income, professional title, psychological empowerment, and hospital ethical climate. Results The total score for operating room nurses’ moral courage in this study was 80.26 ± 19.30, with subscale scores as follows: moral integrity (26.89 ± 6.73), moral responsibility (15.33 ± 3.92), commitment to providing quality care to patients (18.81 ± 4.77), and compassion and genuine presence with patients (19.23 ± 4.86). The moral courage was positively correlated with age, hospital level, years of experience, professional title, income, psychological empowerment and hospital ethical climate score. The multiple linear regression analysis revealed that work meaning, autonomy, work impact, and relationships with nurses, patients, and the hospital being significant factors influencing moral courage. The correlation analysis showed no significant correlation between educational level and moral courage. Furthermore, although nurses with lower income had lower moral courage scores, there was no significant correlation between income satisfaction and moral courage. Conclusion Psychological empowerment and a positive hospital ethical climate are key determinants of moral courage among OR nurses. Hospitals should implement targeted interventions to enhance nurses’ ethical decision-making capacities, foster professional autonomy, and strengthen interpersonal support networks to mitigate ethical distress. Clinical trial number Not applicable.